Dialysis therapy: Its past, present, and future? My personal recollection of dialysis therapy. Issue 1 (May 2019) - Ohira, Seiji; Kukita, Kazutaka
In Dr Ohira's era, hemodialysis was done using an external arteriovenous shunt. External arteriovenous shunts surely made repeated hemodialysis possible, but they also brought about serious complications which necessarily produced the arteriovenous fistula. Arteriovenous fistula is definitely the most important contribution to long-term survival of the hemodialysis patient. Hemodialysis therapy soon became very common, so that various kinds of patients appeared for it. Then came the era of arteriovenous grafts, because many patients lost good vessels in order to create the arteriovenous fistula. More grafts are now becoming available, which are made from different materials and in different forms, thus creating greater expectations for the future. Unfortunately, at this time, the revolutionary vascular access surpassing the arteriovenous fistula has yet to appear and we must continue to make proper application of the arteriovenous fistula. Vascular access is surely one of the important factors to assure a smooth dialysis life for patients. So, we must recognize that we play an important role in the dialysis patients' life. It is interesting to note that in every country, medical care exceeds physical care. This means that the mental factor somewhat compensates for the physical factor. Dr Ohira was a vascular surgeon, but he was also interested in the activities of daily living and quality of life, which must be one of the most delicate fields in medicine.